2014
DOI: 10.3389/fnmol.2014.00069
|View full text |Cite
|
Sign up to set email alerts
|

A central role for ubiquitination within a circadian clock protein modification code

Abstract: Circadian rhythms, endogenous cycles of about 24 h in physiology, are generated by a master clock located in the suprachiasmatic nucleus of the hypothalamus and other clocks located in the brain and peripheral tissues. Circadian disruption is known to increase the incidence of various illnesses, such as mental disorders, metabolic syndrome, and cancer. At the molecular level, periodicity is established by a set of clock genes via autoregulatory translation–transcription feedback loops. This clock mechanism is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 58 publications
(93 reference statements)
2
84
0
Order By: Relevance
“…We propose that without Siah2, RevErb proteins can repress their target genes longer, thereby delaying the activation of these target genes within the clockwork and the start of the next circadian cycle. This same concept explains why loss of rhythmic PER1/2 and CRY1/2 degradation slows circadian clock function (6,7). Consistent with this idea, Ueda and coworkers have shown that strengthening the binding of RevErbα to its response element within the Cry1 promoter can prolong the repression of Cry1 expression and lengthen circadian periods (39).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We propose that without Siah2, RevErb proteins can repress their target genes longer, thereby delaying the activation of these target genes within the clockwork and the start of the next circadian cycle. This same concept explains why loss of rhythmic PER1/2 and CRY1/2 degradation slows circadian clock function (6,7). Consistent with this idea, Ueda and coworkers have shown that strengthening the binding of RevErbα to its response element within the Cry1 promoter can prolong the repression of Cry1 expression and lengthen circadian periods (39).…”
Section: Discussionmentioning
confidence: 75%
“…This loop also drives rhythmic expression of the nuclear hormone receptors RevErbα and RevErbβ (Nr1d1 and Nr1d2, respectively), which in turn rhythmically repress expression of Bmal1, Clock, and Npas2 (3)(4)(5). Circadian expression of core clock genes and their regulated protein degradation are essential for maintaining proper timekeeping (6,7).…”
mentioning
confidence: 99%
“…Many studies have found significant correlations between disrupted circadian rhythms and increased risk for certain cancers, including breast cancer (44). Ubiquitination regulates the stability of core clock proteins; thus, it is possible that this protein interacts with core circadian proteins to regulate rhythms in cell growth and differentiation (45). Again, the role of this protein in the human PFC is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…For the rhythmic expression of clock genes and output (clockcontrolled) genes, both quantity control (amount) and quality control (localization and activity) of the clock proteins are critically important throughout the circadian day. To achieve this rhythmic expression   , clock proteins are precisely controlled by multiple PTMs during the circadian cycle [3][4][5] . Clocks in other organisms, such as Drosophila and Neurospora, have similar feedback loops in which finely tuned PTMs contribute to circadian regulation 3,6 .…”
Section: Instructions For Reviewing Your Article Proofmentioning
confidence: 99%